A brief history of the British Neuroscience Association. (September 2018) - Rose, Steven P.; Allen, Yvonne S.; Varndell, Ian M.
As the British Neuroscience Association commemorates 50 years of existence in 2018, this article recalls its founding as a discussion group, its establishment as the Brain Research Association, its transition to a professional society encompassing all aspects of neuroscience research, both clinical and non-clinical, and its re-branding as the British Neuroscience Association in the late 1990s. Neuroscience as a branch of life science has expanded hugely in the last 25 years and the British Neuroscience Association has adapted, frequently working with partner societies, to serve as an interdisciplinary hub for professionals working in this exciting and crucial field. The authors have attempted to highlight some key events in the Association's history and acknowledge the contributions made by many people over half a century.